Penerapan Model Choo Sense Making Untuk Meningkatkan Sharing Knowledge Pada Laboratorium Media Komunikasi - Devit Setiono (STMIK Budi Darma, 2020)
The Media Communication Laboratory of Budi Luhur University has an assignment to support the learning of students of the Faculty of Communication Sciences (FIKOM). In its development can not be separated from the role of Information technology. The slow and static application of knowledge management makes many knowledge walkouts, plus the change of assistants every year make knowledge and experience not yet documented so that tacit knowledge is still stored in each assistant, causing dependence on senior assistants to solve a problem. The purpose of this study was to determine whether the use of the Choo Sense Making model is appropriate and can be applied to the Media Communication Laboratory. Researchers develop a knowledge management system model that is in accordance with the conditions of the Communication Media Laboratory using the framework of the Tiwana model, the choo sense making model for knowledge formation and integrated with the SECI model at the knowledge creation stage. The results of this study are the design of a knowledge management system model with a choo sense making model to share knowledge through an application through three processes of knowledge formation namely Sense Making, Knowledge Creating, and Decision Making. The results of testing the system using the path analysis model of the Technology Aceptence Model with 5 variables, namely, Perception of Usability, Perceived Ease of Use, Actual Use of the System, Attitude Toward Using and Behavioral Intention to Use shows results above 71,90%, which means the application of knowledge management system model choo sense making can be applied to the Communication Media Laborator